FORMATION OF THE "ENTERPRISE STAFF COMPETITIVENESS" CONCEPT DEFINITION - SHELEST, IEVGENIIA; DANILKOVA, ANASTASIIA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
An analytical review of existing approaches to the definition of "staff competitiveness" is performed in the article. In addition, the actual interpretation of the essence of this concept is also formed. The research of domestic scientists is mainly devoted to the study of labor competitiveness at the macro level. At the same time, the problem of an individual enterprise in a competitive environment is to increase its own competitiveness, as well as increase the competitiveness of its staff. There is a close relationship between the competitiveness of products and the direct competitiveness of the company’s staff is defined. Competitiveness of staff is an integral part of the competitiveness of the enterprise. The company’s management mostly does not pay enough attention to the development of staff competitiveness as a component of enterprise competitiveness. We have formed that the staff competitiveness is a dynamic complex integrated set of its real and potential quantitative and qualitative characteristics and competitive advantages, its ability to apply and implement them in the present and future through the prism of compliance with the needs of society, enterprise and own needs. We believe that this definition is the most complete and universal, suitable for use by economic entities of different levels and forms of ownership, at any time. In our interpretation, we take into account the dynamism, multifaceted and multi-structured competitiveness of staff.